STUDI TINGKAT DINAMIKA KELOMPOK PENGOLAH “Sukses Mandiri” PADA USAHA PENGOLAHAN HASIL PERIKANAN DI PERUMAHAN KELEDANG MAS BARU KECAMATAN SAMARINDA SEBERANG KOTA SAMARINDA - Sri Rahayu; Helminuddin; Eko Sugiharto (2339-1324, 2021)
The dynamics of a group can be used as one of the indicators of interaction dynamics (group relations), both internal and external, in a group to achieve the group’s goal. This study aimed at investigating the dynamics level of “SuksesMandiri” fishery processing group in the fisheries processing business in Keledang Mas Baru housing community, Samarinda Seberang sub-district, Samarinda City. All series of this study was conducted for 6 months starting from February to July 2020, and it was located in Samarinda Seberang sub-district, Samarinda City. The sample was taken based on the census method that all population members (fishery processing group) with five (5) people in total were included as the respondents. Data collection was done by doing observation and conducting an interview using a questionnaire. To measure the dynamics level of the fishery processing group, the data were processed using a Likert scale. It was done by giving a score for each respondent’s answer. The highest score was 3 and the lowest score was 1. The result showed that the dynamics level of “Sukses Mandiri” fishery processing group in the fisheries processing business in Keledang Mas Baru housing community, Samarinda Seberang sub-district, Samarinda City was in the high category (dynamic) with a score of 78.8 at a range of 71 - 90. Keywords: Dynamics of a Group, Sukses Mandiri Fishery Processing Group, Keledang Mas Baru Housing Community